Effect of Irrigation Schedule and Fertilizer Levels on Growth and Yield of Sweet Potato ( Ipomoea batatas L.) - Biswal, S.; Nedunchezhiyan, M.; Mohapatra, P. K. (JOURNAL OF ROOT CROPS, 2017)
The field experiment was conducted for two rabi seasons (2002-03 and 2003-04) at the Instructional Farm, Krishi Vigyan Kendra, Orissa University of Agriculture and Technology, Barachana, Odisha to study the irrigation schedule and fertilizer levels on growth and yield of sweet potato (Ipomoea batatasL.). The experiment was conducted in a split plot design with three replications. The irrigation levels were assigned to the main plots (I1= IW/CPE 0.6, I2= IW/CPE 0.8, I3= IW/CPE 1.0 and I4= IW/PE 1.2) and fertility levels to the sub plots (F1= N-P2O5-K2O @ 0-0-0 kg ha-1, F2= N-P2O5-K2O @ 50-50-50 kg ha-1, F3= N-P2O5-K2O @ 50-50-75 kg ha-1, F4= N-P2O5-K2O @ 75-50-75 kg ha-1, F5= N-P2O5-K2O @ 75-50-100 kg ha-1and F6= N-P2O5-K2O@ 75-50-125 kg ha-1). The variety Sankar was used.The results revealed that different growth parameters (vine length, number of leaves and LAI) and vine yield were greater with frequent irrigation at IW/CPE 1.2 (I4). Application of N-P2O5-K2O @ 75-50-125kg ha-1(F6) resulted in greater vine length, leaf number, LAI and vine yield. Application of irrigation at IW/CPE 0.8 (I2) resulted in greater yield attributes (tuber length, girth and weight per plant), tuber yield, harvest index and water use efficiency. Greater yield attributes (tuber length, girth and weight per plant), tuber yield, harvest index and water use efficiency were recorded with application of N-P2O5-K2O @ 75-50-75 kg ha-1(F4). The maximum tuber yield with optimum vine yield was obtained with the application of N-P 2O5-K2O @ 75-50-75 kg ha-1at IW/CPE 0.8.